Effectiveness of Combination of Tamarind and Saffron as Antidiabetic - Hilda Hilda; Pratiwi Rukmana Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2021)
According to the International Diabetes Federation, 537 million people are currently living with diabetes. There are 316 million people with impaired glucose tolerance at high risk, an alarming number expected to reach 783 million people by 2045. Society's tendency to return to nature is a prospective condition for developing research on biodiversity-based plants. Based on the research results, tamarind leaves are rich in flavonoids, saponins, and tannins, and saffron contains the active compounds crocin, crocetin, and precision, which can be candidates for antioxidants that have a significant effect on blood glucose levels. This antidiabetic research includes research live (test animals) by measuring blood glucose levels. The results showed that tamarind leaf extract and saffron were effective as antidiabetics in male mice induced with Streptozotocin. All extract groups tested single doses of EDAJ, ES, and combination doses of EDAJ and ES ((75:25), (50:50) (25:75)) showed the potential to reduce blood sugar levels >50%. The ES group with a single dose of 100:0 showed significant effectiveness in reducing blood sugar levels from the 6th day until the end of the study. These results are then expected to provide information to the public regarding the potency, effective dose, and working mechanism of using tamarind and saffron as antidiabetics so that they can be a solution to improve the quality of life of diabetes patients, control non-communicable diseases and reduce treatment costs. Keywords: Crocus sativus, Diabetes mellitus, Mus musculus, Saffron, Tamarind leaf